Modification of silica–alkyl phase by cationic surfactant and silica precursor. Issue 1 (16th January 2017) - Sienkiewicz, Andrzej; Krasucka, Patrycja; Goworek, Jacek
Abstract : A new sandwich-type (silica–organic silica) composite in the form of spherical beads or irregular particles was prepared by condensation of tetraethyl orthosilicate on hydrophobic Eurospher-100 C18 and LiChrosorb RP-18 particles. The silica–alkyl composites were characterised by scanning electron microscopy, transmission electron microscopy, atomic force microscopy, nitrogen adsorption porosimetry, X-ray diffraction and thermogravimetric analysis, combined with mass spectrometry. Experimental data indicate that the long hydrocarbon chains of the initial material combined with silica, producing a sandwich-type composite. Additionally, in the surface phase, small microcrystallites of silica, exhibiting very regular pore shape and uniform pore size, were produced. The obtained hybrid material shows some unique features. The advantage of the applied synthesis route is that it gave a new organic–inorganic material which is completely wettable by water and displays the ability to absorb hydrophobic components from a binary aqueous solution. The surface properties were examined by adsorption from binary water solutions. As a model organic adsorbate, metronidazole was chosen.